Sharia Digitalization as a Driver of Financial Inclusion in Remote Areas - Mukhammad Kholid Mawardi; Widya Ningsih (Baca Dulu Publisher, 2025)
The vacuum in Islamic finance education and poor transportation in outlying rural area will be a real challenge for example to equalize the economic on ethical basis backed by Islam Digitisation or internet is now pushing the Islamic finance further and further, with entrepreneurs defining its service to focus on the need which has been articulated as formless but open so that they can skim more through (depth) or across (width) depending entirely from them. This, in turn, provides one way to get around difficulties of geography and topography through fintech development in the form of mobile banking services, Sharia-compliant QRIS-based payment systems—and so on and so forth right down to Islamic law. However, if they can cope with these technical tasks at the plethora of gadgets we already give them then great, there's some benefits for them where currently were none. This study specifically aim to explore the effectiveness of Sharia financial inclusion in rural area by examining the role digitalization, digital literacy and infrastructure. Each of Impact and the model (of warmth): relation in a qualitative descriptive analysis study shows how these three effects impact each other to reinforce Shariah Digital Ecosystem lead to above table The first it` is that digitization accelerates access time for people to get Islamic financial services. A useful implication of this research is that financial institutions (FIs), regulators and governments should develop a digital architecture which have maqāṣid al-syarī'ah at the core for the masses to benefit The novelty to this study lies in combining technology, literacy and infrastructure as means towards achieving sustainable digital transformations among community based Islamic financiers population initiatives.